Dental implant placement with inferior alveolar nerve repositioning in severely resorbed mandibles: a retrospective multicenter study of implant success and survival rates, and lower lip sensory disturbances - George Deryabin; Simonas Grybauskas (SpringerOpen, 2021)
Abstract Background The purpose of this study was to analyze medium-to-long-term implant success and survival rates, and lower lip sensory disturbance after placement of dental implants with simultaneous inferior alveolar nerve (IAN) repositioning. Methods Fifteen patients (3 men, 12 women) treated in two centers were included in this retrospective study. The ages of the participants ranged from 19 to 68. A total of 48 dental implants were placed in 23 posterior mandibular segments simultaneously with IAN transposition or lateralization. The residual bone above the IAN ranged from 0.5 to 7.0 mm. Crestal bone changes were measured using cone beam computed tomography (CBCT) images. Disturbance of the IAN was evaluated subjectively using a modified questionnaire. Results The healing process was uneventful in fourteen patients. In one patient, spontaneous fracture of the operated mandible occurred on tenth day after the surgery. The implant in the fracture line was removed at the time of open reduction and fixation. One more implant was lost after 5 years of loading. Therefore, the overall dental implant survival rate was 95.8%, whereas all implants in function were judged as successful after a follow-up period of 1 to 10 years. Transient neurosensory disturbances (ND) were observed in all patients who underwent IAN lateralization and IAN transposition. At follow-up times of 3 years, 5 years, and 10 years, weak hypoesthesia remained in two subjects treated with IAN transposition. None of the patients developed neuropathic pain after the procedure. Conclusions Within the limitations of this study, we conclude that reconstruction of severely resorbed mandibles with dental implants in conjunction with IAN repositioning is an effective and reliable technique. Although neurosensory disturbances are the most common complication after surgery, they tend to resolve over time. Advanced surgical skills are required to perform this technique.